Psimmenos, Iordanis (ed.) (2017). Special Section: Unveiling Domestic Work in Times of Crisis. Journal of Modern Greek Studies, Volume 35, Number 1, May 2017, pp. 1-128. Johns Hopkins University Press - Galata, Paraskevi-Viviane; Poulou, Eleni (The Greek Review of Social Research, 2017)
Παρουσίαση από την Παρασκευή-Βίβιαν Γαλατά και την Ελένη Πούλου του Psimmenos, Iordanis (ed.) (2017). Special Section: Unveiling Domestic Work in Times of Crisis. Journal of Modern Greek Studies, Volume 35, Number 1.